PEREMPUAN BATAK BURUH TANI SAWIT DI KECAMATAN DAYUN KABUPATEN SIAK - Siregar, Dona Siska; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is entitled â€œBatak Women Palm Farm Workers in Dayun Subdistrict Siak Regency. This study describes the life of the Batak Women Farmers who carry out all their activities with a strong spirit in carrying out their roles in their lives. Being the head of the household or as an addition to the needs of the family, Batak women do not feel burdened what they have been given. The method used in this research is Descriptive Qualitative research method, which discusses this research presented and analyzed in the form of a description of words (descriptive) with a Qualitative approach. In addition, this research is also supported by the implementation of in-depth interviews with informants (informants) that have been determined by the researchers first. From the results of these interviews, the information obtained is very supportive for the validity of the data that is the focus of the research. Based on the results of the study, that the profile of the Batak Women Farmers run their roles like women as usual. However, Batak women who work as farm laborers apply differently to their families in carrying out their roles, in terms of persistence to work so that they can better send their children to school. In addition to working, Batak women also have high solidarity with their fellow Batak ethnic groups, when there are those who need help.Â Keywords : Batak Women, Farm Workers, In Dayun District